(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2016)
This paper investigates the major weaknesses in essentialist art theories including a transformed new version known as the institutional theory. Proponents of the institutional theory like Danto and Dickie believe that the essence of art is a relational (rather than physical) property, with Dickie arguing that the two common characteristics are: (i) the work must be an artefact; and (ii) there must be someone or institution that confers on it the status of object for appreciation. I will show that such institutional theories may describe a necessary property, but never the sufficient property of art. This means that like traditional essentialist theories, they (also) fail to identify the essence of art. I will then argue in support of Morris Weitz's claim that art is an open concept, and its capacity for incorporating very novel and different objects or activities makes it impossible (and a waste of effort) to describe the necessary and sufficient conditions of art.